2019
DOI: 10.1021/acsomega.9b01590
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Hyaluronic Acid Binding to Murine SAA1.1 and SAA2.2

Abstract: Persistently high plasma levels of serum amyloid A (SAA) may induce AA amyloidosis in various organs causing their dysfunction. Although SAA isoforms share a high degree of homology, only the SAA1.1 isoform is found in amyloid deposits. SAA1.1 misfolding is a nucleation-dependent process with dimer and trimer formation playing a major role in SAA fibril formation through self-catalyzed recruitment of native SAA molecules. Yet, a structural model of initial SAA oligomerization is still missing. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…The analysis of the dynamic behavior of key regions identified by RMSF analysis (regions with higher RMSF) in different systems was performed by PyEMMA (Scherer et al, 2015) as previous described (Jin et al, 2019). Briefly, the coordinations of Cα atoms in each region were used to define the initial model, and dimension of input coordinates was reduced by TICA (Time-Lagged Independent Component Analysis) on two dimensions.…”
Section: Trajectory Analysismentioning
confidence: 99%
“…The analysis of the dynamic behavior of key regions identified by RMSF analysis (regions with higher RMSF) in different systems was performed by PyEMMA (Scherer et al, 2015) as previous described (Jin et al, 2019). Briefly, the coordinations of Cα atoms in each region were used to define the initial model, and dimension of input coordinates was reduced by TICA (Time-Lagged Independent Component Analysis) on two dimensions.…”
Section: Trajectory Analysismentioning
confidence: 99%
“…SAA promotes chemotaxis of monocytes and neutrophils and plays a key role in various functions such as lipoprotein metabolism, cholesterol transport, and host defense [19]. Previous studies have shown that SAA1 plasma levels have increased dramatically in response to tissue damage, infection, and various emergencies [20,21]. So SAA1 is also involved in the pathogenesis of SCM, and its mechanism is similar to that of C3.…”
Section: Discussionmentioning
confidence: 99%
“…MM-GBSA analysis of molecular dynamics trajectories seeded with various docked conformations of glycosaminoglycans showed that hyaluronan could simultaneously bridge both proteins in the MMP2/TIMP3 complex and stabilize the complex to increase MMP2 activity, unlike other glycosaminoglycans [ 178 ]. Two different forms of serum amyloid A protein, only one of which is found in amyloid deposits, were independently simulated with hyaluronan, and these microsecond-scale trajectories showed distinct hyaluronan binding patterns that may be important to the initial protein oligomerization leading to amyloid formation [ 179 ]. The polysaccharide lyase from the Stenotrophomonas maltophilia bacterium has pH-dependent activity against three chemically dissimilar carbohydrates, including hyaluronan, and simulation data directly correlated stability of hyaluronan–protein binding at various pH values with hyaluronan lyase activity of the enzyme as a function of pH [ 180 ].…”
Section: Atomic-resolution Molecular Dynamics Simulations Of Hyaluron...mentioning
confidence: 99%